2020
DOI: 10.1186/s12883-020-1601-2
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of pleomorphic xanthoastrocytoma and differential diagnosis: case report

Abstract: Background: Pleomorphic xanthoastrocytoma (PXA) is a rare astrocytic glioma, characterized by large pleomorphic and frequently multinucleated cells, spindle and lipidized cells, a dense pericellular reticulin network, and numerous eosinophilic granular bodies according to the grade II glial tumor standards of the World Health Organization's (WHO) 2016 guidelines. PXA rarely transforms into anaplastic PXA or glioblastoma (GBM) and anaplastic PXA, classified as WHO grade III, has a more aggressive clinical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Case studies have identified eGBM arising from PXA. 40 Our findings are broadly consistent with prevalence estimates presented in the WHO guidelines. 41 WHO categorises DIA and DIG subtypes together; we have found the prevalence of BRAFV600 mutation to be somewhat higher in DIA, compared with DIG.…”
Section: Discussionsupporting
confidence: 90%
“…Case studies have identified eGBM arising from PXA. 40 Our findings are broadly consistent with prevalence estimates presented in the WHO guidelines. 41 WHO categorises DIA and DIG subtypes together; we have found the prevalence of BRAFV600 mutation to be somewhat higher in DIA, compared with DIG.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the existing literature includes both pediatric and adult cases where APXA was either challenging to diagnose or misdiagnosed as either low-grade tumors or WHO grade 4 gliomas. 3 , 12 , 18 , 24–26 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 6 , 7 Furthermore, BRAFV600E mutation has also been most commonly described in PXA and APXA. 3 , 8 , 9 …”
mentioning
confidence: 99%
“…A-PXA and E-GBM are similar in histology, immunohistochemistry, molecular and clinical characteristics. Although PXA rarely transforms into A-PXA or GBM [8], there have been some related studies of PXA transformed into GBM so far, for example, 1) a case of secondary disease with an IDH1 mutation had been reported, which is a common type of molecular feature of secondary GBM secondary to astrocyte tumors [2]. 2) Shingo Tanaka et al described a case of E-GBM developing at the site of a previously resected PXA with the BRAF V600E mutation 13 years after the initial surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, 5%-20% of patients with PXA have a recurrence with malignant transformation. PXA rarely transforms into anaplastic pleomorphic xanthoastrocytoma (A-PXA) or glioblastoma (GBM) [8].…”
Section: Introductionmentioning
confidence: 99%